Bimbingan Kelompok Berbasis Ajaran Islam Untuk Meningkatkan Pemahaman Mahasiswa Tentang Karakteristik Kepemimpinan Dalam Pandangan Islam - Zhila Jannati (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
Leadership is needed by every individual so that an activity carried out in daily life can be directed and well organized so that it can achieve predetermined goals. In this case, Islam as a religion of rahmatan lil 'alamin has regulated how leadership characteristics can lead humans not only to the achievement of worldly goals but will also bring people to their true goals, namely the hereafter. The purpose of this study is to find out how Islamic teaching-based group guidance improves understanding of leadership characteristics in the view of Islam. This research uses qualitative research methods while the data collection techniques in this study are documentation techniques. The subjects in the study were 10 students from the Islamic Guidance and Counseling study program, Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. Data were analyzed using qualitative descriptive analysis. The results of this study are (a) Islamic teaching-based group guidance has been carried out through four stages namely the formation stage, the transition stage, the activity stage, and the termination stage, and (b) The students' understanding of the characteristics of leadership in Islam which includes siddiq, tabligh, amanah and fathonah have increased after the implementation of group guidance based on Islamic teachings.